Computer simulations of the interactions of the (0 1 2) and (0 0 1) surfaces of jarosite with Al, Cd, Cu2+ and Zn - Hudson-Edwards, K.; Wright, Kathleen (Pergamon-Elsevier Science Ltd, 2011)
Jarosite is an important mineral on Earth, and possibly on Mars, where it controls the mobility of iron, sulfate and potentially toxic metals. Atomistic simulations have been used to study the incorporation of Al3+, and the M2+ impurities Cd, Cu and Zn, in the (0 1 2) and (0 0 1) surfaces of jarosite. The calculations show that the incorporation of Al on an Fe site is favorable on all surfaces in which terminal Fe ions are exposed, and especially on the (0 0 1) [Fe3(OH)3]6+ surface. Incorporation of Cd, Cu or Zn on a K site balanced by a K vacancy is predicted to stabilize the surfaces, but calculated endothermic solution energies and the high degree of distortion of the surfaces following incorporation suggest that these substitutions will be limited. The calculations also suggest that incorporation of Cd, Cu and Zn on an Fe site balanced by an OH vacancy, or by coupled substitution on both K and Fe sites, is unfavorable, although this might be compensated for by growth of a new layer of jarosite or goethite, as predicted for bulk jarosite. The results of the simulations show that surface structure will exert an influence on uptake of impurities in the order Cu > Cd > Zn, with the most favorable surfaces for incorporation being (0 1 2) [KFe(OH)4]0 and (0 0 1) [Fe3(OH)3]6+.